1997
DOI: 10.1038/sj.bjp.0701348
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of adenylyl cyclase by octopamine via a human cloned α2A‐adrenoceptor

Abstract: 1 In this study we have compared the abilities of the enantiomers of the structural isomers of the phenolamines, octopamine and synephrine, and the catecholamines, noradrenaline and adrenaline, to couple selectively a human cloned a 2A -adrenoceptor, stably expressed in a Chinese hamster ovary (CHO) cell line, to G-protein linked second messenger pathways mediating an increase and a decrease in cyclic AMP production. 2 The catecholamines couple the a 2A -adrenoceptor to both an increase and a decrease in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 25 publications
(42 reference statements)
3
30
2
Order By: Relevance
“…At higher concentrations of (7)-noradrenaline the inhibitory e ects of the agonist were not signi®cantly altered. In contrast to some previous studies (Fraser et al, 1989;Eason et al, 1992;Airriess et al, 1997;Rudling et al, 1999) in the transfected cell line used in this study, with a lower expression level, the coupling of the a 2A -adrenoceptor to cyclic AMP production did not display a biphasic appearance. However, after 24 h pre-incubation with PTX, the inhibition of cyclic AMP production was abolished and replaced by a signi®cant stimulation (F=7.24; d.f.=6,31; P50.001) with a maximum e ect at an agonist concentration of 1 mM (161.1+10.8% of control value; n=5) ( Figure 1A).…”
Section: Results a 2a -Adrenoceptor Cyclic Amp Responsecontrasting
confidence: 99%
See 1 more Smart Citation
“…At higher concentrations of (7)-noradrenaline the inhibitory e ects of the agonist were not signi®cantly altered. In contrast to some previous studies (Fraser et al, 1989;Eason et al, 1992;Airriess et al, 1997;Rudling et al, 1999) in the transfected cell line used in this study, with a lower expression level, the coupling of the a 2A -adrenoceptor to cyclic AMP production did not display a biphasic appearance. However, after 24 h pre-incubation with PTX, the inhibition of cyclic AMP production was abolished and replaced by a signi®cant stimulation (F=7.24; d.f.=6,31; P50.001) with a maximum e ect at an agonist concentration of 1 mM (161.1+10.8% of control value; n=5) ( Figure 1A).…”
Section: Results a 2a -Adrenoceptor Cyclic Amp Responsecontrasting
confidence: 99%
“…However, the results di er to previous studies involving CHO, HEK293, PC-12 and JEG-3 cells, where activation of a 2A -adrenoceptors by noradrenaline resulted in a biphasic response in cyclic AMP production (Fraser et al, 1989;Duzic & Lanier, 1992;Eason et al, 1992;Pepperl & Regan, 1993;Svensson et al, 1996;Airriess et al, 1997;Jasper et al, 1998;Rudling et al, 1999). The receptor-mediated stimulation of adenylyl cyclase activity in CHO cells has previously been attributed to high receptor expression levels (Eason et al, 1992).…”
Section: Discussioncontrasting
confidence: 98%
“…Both the PI3K pathway (Scheid and Woodgate, 2001) and catecholamines (Pendelton et al, 1997) are known to have important roles in the control of Drosophila development, and, in addition, the activation of the MAPK pathway is an important regulator of cellular differentiation in Drosophila (Bier, 1998). A wide range of other Drosophila GPCRs, including the OA/TYR receptor (Robb et al, 1994), the DopR99B D 1 -like DA receptor (Reale et al, 1997), and the short neuropeptide F receptor , have also been shown to exhibit various forms of agonist-specific coupling, as have several vertebrate adrenergic and neuropeptide GPCRs (Spengler et al, 1993;Airriess et al, 1997). It remains to be determined whether both DA and the ecdysteroids can signal or modulate each other's actions through DmDopEcR in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP assays. CHO cells stably expressing DmDopEcR or the Drosophila Oct/Tyr receptor (Arakawa et al, 1990) and wild-type cells were incubated with agonist in the presence of forskolin and isobutyl-3-methylxanthine (IBMX), as described previously (Airriess et al, 1997). Sf9 cells infected with DmDopEcR were harvested 48 h after infection and incubated with various concentrations of agonists in the presence of forskolin and IBMX, as described previously (Bandoh et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…noradrenaline, lead to stimulation of both G i -and G s -dependent pathways, whereas monohydroxylated agonists, e.g. octopamine, lead only to activation of G i -dependent pathways (47).…”
Section: Discussionmentioning
confidence: 99%